Study on Critical Success Factors Estimation in IT System Development (Sains Humanika, 2017)
The success of IT system development largely depends on the System Requirements Definition (SRD) phase. Researches on Critical Success Factors (CSFs) in the SRD phase are very few. This paper aims to make clear the CSFs in the SRD phase of IT system development. To achieve this, first, interviews to discover â€œdifficult itemsâ€ in the SRD phase were executed to participants who were engaged in three highly advanced IT system developments. Second, major difficult items were extracted from the interview results. Third, CSFs estimation was executed from the extracted major difficult items. Then, the estimated CSFs were compared to those obtained from the interviews. As a result, CSFs were found to be almost the same between those estimated and interviewed. Through this research, it can be concluded that 1) Customer/User Involvement, 2) Clear project goals, and 3) Technical skills of the project team are the major CSFs in the SRD phase
Keywords: IT system; critical success factors; system requirements definition; system development